Pengaruh Penyebaran Corona Virus Disease (Covid-19) pada Pendapatan Masyarakat Nelayan di Kabupaten Cilacap - Kristian Cahyandi (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
One of the factors considered to affect the economic level of the fishing community in terms of income fluctuations is the Covid-19 pandemic. This study aims to analyze the income of fishermen during the Covid-19 pandemic in 2021 in the Cilacap Regency area. The method used is a case study using trend analysis (time series) by utilizing quantitative descriptive research. The results of the study revealed that some staple foods did not directly affect the income of fishermen using motorboats. Meanwhile, the price of diesel fuel directly affects the income of fishermen. The income of fishermen during the COVID-19 pandemic has decreased due to low fish prices. It can be concluded that the Covid-19 pandemic has indirectly impacted the income of fishermen in Cilacap Regency as a result of the decline in the selling price of fish, although the number of catches depends on the wind season. So that there is a need for further handling from the government in providing certainty and protection for the sustainability of fishing business in Cilacap Regency in the future, in the form of forming groups of fishermen so that fish catches can be sold in the market together so as to reduce transportation costs. The sale of fish in the market can increase the acquisition of a higher price compared to being sold at middlemen. Create a savings and loan cooperative to provide loans when fishermen experience a decrease in income. And finally, by directing fishermen to process their catch in advance so that a higher selling value can be obtained.